Dimethyl carbonate as a non-innocent benign solvent for the multistep continuous flow synthesis of amino alcohols. Issue 4 (12th July 2018) - Porcar, Raul; Lozano, Pedro; Burguete, Maria Isabel; Garcia-Verdugo, Eduardo; Luis, Santiago V.
Abstract : An efficient methodology for the production and resolution of amino alcohols with a low environmental impact has been developed. Abstract : An efficient methodology for the production and resolution of amino alcohols with a low environmental impact has been developed. The system is based on the assembly of three different well compartmentalised catalytic modules allowing the combination of catalytic and biocatalytic elements. Dimethyl carbonate is used as a green but non-innocent solvent, playing a dual role as the solvent and reagent for two out of the three synthetic steps considered. The use of polymer-supported ionic liquids (SILLPS) is key for the development of some of the catalytic systems optimised.